The social sustainability of cities : diversity and the management of change - Polèse, Mario, 1943-; Stren, Richard E. (University of Toronto Press, 2000)
Some cities have been more successful than others in creating environments conducive to the cohabitation of a diverse population. Case studies analyze ten cities in North America, South America, Europe, and Africa in terms of their social sustainability.
Keywords: Sociology, Urban.; Cities and towns -- Growth.; Small cities -- Growth.; Sociologie urbaine.; Petites villes -- Croissance.; Villes -- Croissance.; urban sociology.; SOCIAL SCIENCE -- Sociology -- Urban.; Cities and towns -- Growth; Sociology, Urban; Stadtsoziologie; Aufsatzsammlung; e-books.; Livres numériques.